Parenting stress and family functioning of commuter family in Malaysia - Arshat, Zarinah; Pai, Farah Syuhada; Ismail, Zanariah; Baharudin, Rozumah (Canadian Center of Science and Education, 2016)
This study aims to determine relationship between parenting stress and family functioning as well as to explore the effects of gender on the aforementioned stress and functioning variables among commuter family. A total of 72 couples of commuter family were involved in this study. Result showed that higher parenting stress relate to less satisfactory family functioning. The study also revealed that there was no significance differences in perception on parenting stress and family functioning between husband and wife of commuter family. Government and non-government sectors can used the results of the study to provide programs that can help commuter families to deal and cope with the challenges. Finally, future research is needed to take in-depth look with other variable exists and replicated with different population.